PENGALAMAN KEAGAMAAN PARA GURU PENDIDIKAN AGAMA ISLAM - Fuad Nashori; R. Rachmy Diana (Psikis : Jurnal Psikologi Islami, 2018)
This study intends to get an overview of the themes and processes of religious experience in Islamic religious education teachers. Data disclosure of research respondents, namely religious teachers, was carried out using in-depth interviews. The results showed that the research respondents had a variety of religious experiences, both physiological, social-psychological, parapsychological, and spiritual. Among the various experiences above, the most prominent theme is the themes of experience of the mind. Various spiritual experiences take place through a process that involves socio-cultural conditions, opportunities, difficulties and challenges of life, worship such as praying, tahajjud prayer, diligent prayer, timely prayer, positive behavior or attitude towards others, and the nearest social environment such as brothers, uncles / mother, and so on.